Online Media Trend as a Promotional Tool - Tasruddin, Ramsiah (Jurnal Mercusuar, 2021)
The transformation of marketing activities in the digital era has become a profitable opportunity. Most businesses, from small to medium and large scale, have become aware of utilizing the available technology in social networking sites for promoting their products, goods, and services. Not a few successful entrepreneurs have emerged from adapting to the development of business that utilizes social media as a platform for promoting their products, goods, and services